A community for students. Sign up today!
Here's the question you clicked on:
 0 viewing

This Question is Closed

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0( cost)' ? (sint)' ?

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0> b ( cos t ) ' =  bsint Okie, so far?

Shriya
 2 years ago
Best ResponseYou've already chosen the best response.1y=bcost+t2sint differentiating w.r.t t, dy/dt= bsint+ d/dt(2tsint) now, we have to differentiate 2tsint using product rule for derivative. so, the derivative of 2tsint becomes (2tcost+2tsint) therefore, dy/dt= bsint+2tsint+2tcost taking sint common, dy/dx=sint(2b)+2tcost

v.s
 2 years ago
Best ResponseYou've already chosen the best response.0but i understand what you did

Shriya
 2 years ago
Best ResponseYou've already chosen the best response.1datz ok! :) not a big deal. derivatives is realy easy as compared to the other sections of calculus. u jus need 2 know the ways to differentiate! :)

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0Apply product rule here ( t²* sin t ) ' with : u = t² > u' = ... v = sint > v' = ....

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0@v.s Do you know product rule?

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0Yep, now put the 2 results together :) y' = ....

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0y = b cos t + t² sin t >y' = ...

v.s
 2 years ago
Best ResponseYou've already chosen the best response.0y"= bcost+2t*sint+cost*t^2

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0y = b cos t + t² sin t > b ( cos t ) ' =  bsint > ( t² sin t )' = 2t sint+ t² cost

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0What's my instruction above?

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0The product rule applied to take derivative of the second term!

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0y = b cos t + t² sin t > b ( cos t ) ' =  bsint ( derivative of the first term) > ( t² sin t )' = 2t sint+ t² cost ( derivative of the second term)

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0Yep, now put the 2 results together :) y = b cos t + t² sin t y' =  bsint + 2t sint+ t² cost

Chlorophyll
 2 years ago
Best ResponseYou've already chosen the best response.0Now you can make it neat by simplifying  bsint + 2t sint together.
Ask your own question
Ask a QuestionFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.